A STUDY OF THE ACADEMIC LEADERSHIP OF SCHOOL ADMINISTRATORS UNDER THE BURIRAM EDUCATIONAL SERVICE AREA OFFICE 3 - Sarasri, Phongsatorn (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were 1) to study the level of academic leadership of school administrators and 2) to compare academic leaderships of school administrators classified types of school and administration experiences. The sample group was 417 people included A school administrator, A deputy school administrator and a teacher from academic department aunder Buriram Primary School Educational Service Area Office 3 selected by stratified random sampling. The research instrument were a set of five- rating scale questionnaires about school administrators’ academic leadership under Buriram Primary School Educational Service Area Office 3 based on Likert Scale. The questionnaire’s IOC index range was at 0.80 - 1.00 and the overall reliability was at 0.96. The analyzing statistics were percentage, mean, standard deviation, t-test and sing F-test in Scheffe’s Method; in the case that the differences were found from pair comparisons. The results of this study provided 1. The overall rate of school administrators’ academic leadership was at a high level. When considering each aspect, found that all aspects are at a high level. 2. The overall academic leadership of school administrators categorized by school types is statistically significant differences at the 0.5 level of significant. Furthermore, the academic leadership of school administrators classified by school administrators’ administration experiences are no different.